Gallbladder cancer – no improvement in survival over time in a Swedish population - Lindnér, Per; Holmberg, Erik; Hafström, Lo (Acta oncologica, 2018)
Gallbladder cancer (GBC) has an extremely poor outcome. The aim of this study was to examine trends in GBC incidence, treatment and overall survival in a complete population of affected persons in a well-defined region in Sweden in 2000-2014. Altogether 546 individuals with GBC were identified at Sweden's Regional Cancer Centre West. Subjects were grouped into three 5-year periods (Period A: 2000-2004, Period B: 2005-2009 and Period C: 2010-2014) and the survival, diagnosis, staging, grading and treatment for each period were investigated. Patients dead at date of diagnosis (n = 39) and patients with not invasive cancer (n = 25) were not included in the analysis. The incidence was unchanged over the study period. The survival curves for the time periods were not significantly separated. Median survival was 4.7 months in Period A, 4.8 months in Period B and 6.1 months in Period C. Stage migration to more M1 in Periods B and C occurred and survival was improved for these cohorts. More individuals were diagnosed using only diagnostic imaging (p = .02). There were 177 curatively aiming operative procedures carried out on 482 persons (37%). The survival after surgery for the three periods improved over time (p = .02). Individuals who underwent a liver bed resection after a cholecystectomy had better survival than individuals who had cholecystectomy combined with liver resection. More persons were treated with chemotherapy, but no significant impact was found on survival in the total GBC population. Although there were signs of improved diagnosis of GBC, the survival rate did not improve over time. There was a significant stage migration to more M1 in Periods B and C. Therapeutics able to downsize a cancer and increase the effectiveness of surgery with curative intent are warranted.